PENERAPAN MODEL PEMBELAJARAN ADVANCE ORGANIZER DENGAN METODE MIND MAP TERHADAP KETERAMPILAN BERPIKIR ANALISIS SISWA KELAS X PADA KONSEP EKOSISTEM DI SMA NEGERI 1 DARMA - Ading Supriadi; Anna Fitri Hindriana; Haruji Satianugraha (Program Studi Pendidikan Biologi, FKIP Universitas Kuningan, 2016)
The background of this research is still a lot of learning with teacher centered paradigm. Such a paradigm would lead to less students master the concepts learned. Lack of mastery of concepts can lead to students not mastering the skills of thinking. One of the skills of thinking is analytical thinking. The problem arises from an idea to apply the learning model with the Advance Organizer and Mind Map method to the analysis of students' thinking skills class X on the ecosystem concept in SMA Negeri 1 Darma. This study used a quasi-experimental method with experimental classroom using learning model Advance Organizer with the Mind Map method while the control class using conventional learning models. This study was implemented on 64 students of class X SMA Negeri 1 Darma, with descriptions of 37 students in the experimental class and 37 students in the control class. Analytical thinking skills measured by objective tests using the excuse that includes questions thinking skills of analysis, objective tests are given at the time of the pretest and posttest. The average value of objective tests in the experimental classes while pretest 26.40 and 62.07 posttest while the control class while pretest, posttest 27.12 and 44.41. Testing hypotheses based on the results of objective tests using Wilcoxon test. Based on calculations using the test results obtained pretest Wilcoxon Wcount 235 and Wtable means Wcount Wtable, 242 means there is no difference between the control and eksperimen, class at posttest results obtained Wcount 674 and then Wcount Wtable 242, meaning that there is a difference between the control and the class after the experiment. It can be concluded that there is a real effect of the application of the learning model Advance Organizer with the Mind Map method to the analysis thinking skills of students' class X.Keywords: Advance Organizer, Mind Map, Analysis Thinking